2009
DOI: 10.1177/0883073808325657
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Acute Transverse Myelitis: Clinical Profile, Outcome, and Association With Antiganglioside Antibodies

Abstract: Prospectively, in 15 children the association of acute transverse myelitis with Campylobacter jejuni infection and antiganglioside antibodies was studied. The clinical profile, radiological findings, and treatment outcome in these children were analyzed. Stool culture and serology for Campylobacter jejuni and antiganglioside antibodies were tested. In all, 15 age- and sex-matched healthy controls were tested for evidence of Campylobacter jejuni infection and antiganglioside antibodies. Anti-GM1 antiganglioside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…We have also earlier reported a corelation of GBS with C. jejuni in the same study population; antecedent C.jejuni infection was found in 27.7% of GBS patients as compared with 2.3% in neurological controls and 2.3% in non-neurological controls [20,21] In the present study, we found that 12 out of 57 GBS patients (21.05%) had recent M. pneumoniae infection (IgM antibodies positive) as compared to 14.2% each in the neurological and non-neurological controls. This difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 76%
“…We have also earlier reported a corelation of GBS with C. jejuni in the same study population; antecedent C.jejuni infection was found in 27.7% of GBS patients as compared with 2.3% in neurological controls and 2.3% in non-neurological controls [20,21] In the present study, we found that 12 out of 57 GBS patients (21.05%) had recent M. pneumoniae infection (IgM antibodies positive) as compared to 14.2% each in the neurological and non-neurological controls. This difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 76%
“…[5][6][7][8][9] Descriptive case series and consensus statements in pediatric neuroinflammatory conditions support treatment of acute neuroinflammatory events with intravenous methylprednisolone 30 mg/kg (to a maximum of 1 g) daily for 3 to 5 days. 8,[10][11][12] Use of high-dose oral corticosteroids in place of intravenous methylprednisolone is not well described in pediatric populations, but adult studies have demonstrated equivalent clinical efficacy between methylprednisolone 1,000 mg/day administered either orally or intravenously in the treatment of MS relapses. 13 In some series, based on the theoretical potential for greater bloodbrain barrier penetration, dexamethasone at IV doses up to 8 mg/day or oral doses up to 16 mg/day have been used.…”
Section: Acute (Induction) Therapymentioning
confidence: 99%
“…Based on the experience with acute inflammatory demyelinating polyneuropathy, investigators in India sought to determine whether Campylobacter jejuni and subsequent development of anti-GM1 antibodies might be associated with pediatric ATM (Kalra et al, 2009). This prospective study examined the possible association of anti-GM1 antiganglioside antibodies in 15 children with ATM and 15 age-and sex-matched controls.…”
Section: Possible Infectious Etiologiesmentioning
confidence: 99%